PENGANGKUTAN KAYU DENGAN TRUK DI KPH BOJONEGORO DAN SARADAN - Apul Sianturi; Dulsalam Dulsalam (Jurnal Penelitian Hasil Hutan, 1985)
An observation on wood transportation by truck has been carried out in the Bojonegoro and Saradan Forest Districts.  Trucks are MercedesBenz, consistingof models rangingfrom 1970 to 1975.The annual operation days of truck at the Bojonegoro and Saradan Forest Districts are 147 and 193  days respectively. The average annual hauling capacity of trucks in Bojonegoro and Saradan is 14 964 tonkm per year and 41 145 tonkm per year respectively.The average hauling cost in Bojonegoro and Saradan is Rp.  300,  per tonkm  and Rp.  107, per tonkm respectively.  This cost is broken down into the following components: Fuel, 9 percent; grease, 9 percent; spare parts,  55 percent; tyres,  23 percent; miscellaneous, 4 percent.